PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN DALAM MENYEWA DI PASAR BOTANIA 2 - Kelsen, Kelsen; Syaifullah (SCIENTIA JOURNAL, 2022)
Rental business is a very profitable business nowadays. By paying attention to service quality and price can create customer satisfaction to the company and their loyalty will also increase. These aims of these studies were for determining the effected of service quality and price on loyalty through customer satisfaction at Pasar Botania 2 Batam used simple random sampling with 104 respondents which collected by distributing questionnaires. These studies use validities and reliabilities tests, classical assumption tests and influence tests also used path analysis and coefficient of determination analysis, while hypothesis testing on these studies uses t test, f test and Sobel test which is processed using SPSS version 25. The results of the t test show that service quality has a significant effect on customer satisfaction, the price value has a significant effect on customer satisfaction, service quality has a significant effect on customer loyalty, the price has a significant effect on customer loyalty, and customer satisfaction has a significant effect on customer loyalty. While Sobel test results show that service quality has an indirect effect on loyalty through customer satisfaction and the price has an indirect effect on loyalty through customer satisfaction.